The Use of Germinants to Potentiate the Sensitivity of Bacillus anthracis Spores to Peracetic Acid - Celebi, Ozgur; Buyuk, Fatih; Pottage, Tom; Crook, Ant; Hawkey, Suzanna; Cooper, Callum; Bennett, Allan; Sahin, Mitat; Baillie, Leslie (Frontiers in Microbiology, 2016)
Elimination of Bacillus anthracis spores from the environment is a difficult and costly process due in part to the toxicity of current sporicidal agents. For this reason we investigated the ability of the spore germinants L-alanine (100 mM) and inosine (5 mM) to reduce the concentration of peracetic acid (PAA) required to inactivate B.anthracis spores. While L-alanine significantly enhanced (p=0.0085) the bactericidal activity of 500 ppm PAA the same was not true for inosine suggesting some form of negative interaction. In contrast the germinant combination proved most effective at 100 ppm PAA (p=0.0009). To determine if we could achieve similar results in soil we treated soil collected from the burial site of an anthrax infected animal which had been supplemented with spores of the Sterne strain of B.anthracis to increase the level of contamination to 104 spores/g. Treatment with germinants followed one hour later by 5000 ppm PAA eliminated all of the spores. In contrast direct treatment of the animal burial site using this approach delivered using a back pack sprayer had no detectable effect on the level of B.anthracis contamination or on total culturable bacterial numbers over the course of the experiment. It did trigger a significant, but temporary, reduction (p<0.0001) in the total spore count suggesting that germination had been triggered under real world conditions. In conclusion, we have shown that the application of germinants increase the sensitivity of bacterial spores to PAA. While the results of the single field trial were inconclusive, the study highlighted the potential of this approach and the challenges faced when attempting to perform real world studies on B.anthracis spores contaminated sites.